Randomised trial on performance, safety and clinical benefit of hyaluronic acid, hyaluronic acid plus dexpanthenol and isotonic saline nasal sprays in patients suffering from dry nose symptoms. Issue 3 (June 2020) - Thieme, Uta; Müller, Karolina; Bergmann, Christoph; Bock, Bernward; Wurzer-Materna, Nadine; Shahab, Taufik; Zeman, Florian; Eberhardt, Yvonne; Huppertz, Gunnar; Koller, Michael; Meiser, Peter
Abstract: Objective: Limited data exist on the clinical benefits of nasal applications for moistening the nasal mucosa. We therefore investigated the effects of hyaluronic acid, hyaluronic acid plus dexpanthenol and isotonic saline nasal sprays in patients suffering from dry nose symptoms in an otorhinolaryngological outpatient setting. Methods: 240 patients were randomised into this prospective, three-armed clinical trial with two assessment points (baseline and 4 weeks later). Patients received either hyaluronic acid, hyaluronic acid plus dexpanthenol or isotonic saline nasal spray over a period of four weeks. Rhinitis Sicca Symptom Score (RSSS) was assessed as primary endpoint, and individual symptoms and tolerability of all treatments as secondary endpoints. Patient perceptions after first application of the allocated nasal spray were recorded using the Nasal Spray Sensory Scale. Treatment effects were analysed for each study arm first and subsequently compared against each other. Results: RSSS (hyaluronic acid: mean difference = 8.90 [98.33% CI = 7.34/10.45]; hyaluronic acid plus dexpanthenol: mean difference = 8.42 [98.33% CI = 6.91/9.94]; isotonic saline: mean difference = 8.94 [98.33% CI = 7.33/10.54]), individual symptoms and Endoscopy Score improved significantly ( p  < 0.001) in all treatment arms. Tolerability was assessed as "flawless" in more than 85% of all treatments, which is reflected in overall high rankings in the Nasal Spray Sensory Scale. Perception of nasal moisturisation was reported to be significantly higher in patients receiving hyaluronic acid plus dexpanthenol as compared to patients receiving hyaluronic acid or isotonic saline. No further significant differences were observed between the three treatments. Conclusion: All three tested sprays (hyaluronic acid, hyaluronic acid plus dexpanthenol and isotonic saline) proved to be suitable treatments for patients suffering from dry nose symptoms. (DRKS-ID: DRKS00013357)